Implementation of Human Resources Planning and Development in Preparing for the Era of Society 5.0 - Pasihul Lisan; Mochammad Isa Anshori (SAJMR : Southeast Asian Journal of Management and Research, 2024)
An era where more and more changes occur in the order of life. The number of changes that occur makes everyone have to be able to adapt to all the changes that exist as well as in organizations. In implementing human resource planning and development, it also changes in accordance with the times. For this reason, the organization must also always be ready and future-oriented so that the organization is able to face all the changes that will occur in the era of society 5.0 so that the organization is able to implement human resources effectively and efficiently so that it can be utilized and can be implemented in the era of society 5.0. This research uses a literature study method where the data is collected from various sources from articles and books and other literature which will later be analyzed and concluded. From the results of the literature study that has been analyzed, it shows that increasing digital skills, adapting to changing industry needs, talent retention, partnerships with educational institutions, flexible work policies, reducing the digital divide, and increasing innovation and competitiveness are some of the positive results achieved. the right strategy, organizations can create a skilled, adaptive, and innovative workforce, ready to contribute to a smarter and more sustainable society